Deciphering the effect of a Cu(II)‐hydrazone complex on intracellular cell signalling pathways in a human osteosarcoma 2D and 3D models - Balsa, Lucia Mariana (2024)
New therapeutic strategies for osteosarcoma (OS) have demonstrated the potential efficacy of copper compounds as anticancer drugs and as a substitute for the often used platinum compounds. OS is a type of bone cancer, primarily affecting young adults and children..The main objective of this work is to discover the molecular targets and cellular pathways related to the antitumor properties of a Cu(II)-hydrazone toward human OS 2D and 3D systems. Cell viability study using MG-63 cells was evaluated in OS monolayer and spheroids. CuHL significantly reduced cell viability in OS models (IC50 2D: 2.6 ± 0.3 µM; IC50 3D: 9.9 ± 1.4 µM) (p<0.001). Also, CuHL inhibits cell proliferation and it induces cells to apoptosis. The main mechanism of action found for CuHL are the interaction with DNA, genotoxicity, the ROS generation and the proteasome activity inhibition. Besides, 67 differentially expressed proteins were found using proteomic approaches. Of those 67 proteins, 40 were found overexpressed and 27 underexpressed. The response to stress and to unfolded protein, as well as ATP synthesis were the most affected biological process among upregulated proteins, whilst proteins related to DNA replication and redox homeostasis were downregulated.